Volume 1: Turbomachinery 1995
DOI: 10.1115/95-gt-079
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamics of a Centrifugal Compressor Impeller With Transonic Inlet Conditions

Abstract: Performance and laser measurement results are presented for a transonic centrifugal compressor stage, equipped with a backswept rotor designed for 586 m/s tip speed and a mean relative inlet tip Mach number of 1.30. ft

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…The first reported measurements were obtained by Eckardt (1976) using a Laser-2-Focus Velocimeter. Since then, several other researchers ( Adler and Levy, 1979;Eckardt, 1979;Krain, 1981Krain, , 1987Ahmed and Elder, 1990;Pak et al, 1993;Krain et al, 1995) have used laser anemometers to measure the flow fields within high-speed centrifugal impellers configured with both vaned and vaneless diffusers. Hathaway et al (1993) reported results from a study in a large low-speed compressor.…”
Section: Introductionmentioning
confidence: 99%
“…The first reported measurements were obtained by Eckardt (1976) using a Laser-2-Focus Velocimeter. Since then, several other researchers ( Adler and Levy, 1979;Eckardt, 1979;Krain, 1981Krain, , 1987Ahmed and Elder, 1990;Pak et al, 1993;Krain et al, 1995) have used laser anemometers to measure the flow fields within high-speed centrifugal impellers configured with both vaned and vaneless diffusers. Hathaway et al (1993) reported results from a study in a large low-speed compressor.…”
Section: Introductionmentioning
confidence: 99%
“…Its geometry specification has been given by Appl. Sci. 2017, 7, 1081 8 of 22 Eisenlohr et al [36] and its measurement results have been provided by Krain et al [37]. The compared pressure curves are at 60%, 70% and 80% of design speeds, where the operating pressure ratios are similar to the investigated case.…”
Section: Validationmentioning
confidence: 73%
“…To further validate the numerical method for predicting performances and detailed flow fields of impellers with vaneless diffusers, the open transonic centrifugal compressor SRV2-O has been investigated applying the same numerical method. Its geometry specification has been given by Eisenlohr et al [36] and its measurement results have been provided by Krain et al [37]. The compared pressure curves are at 60%, 70% and 80% of design speeds, where the operating pressure ratios are similar to the investigated case.…”
Section: Validationmentioning
confidence: 96%
“…The experimental data reported by Krain et al [22] used to validate the numerical model. Computational results of the compressor pressure ratio have been compared with the experimental data in Figure 5.…”
Section: Numerical Model Validationmentioning
confidence: 99%